PENGARUH KECERDASAN MUSIKAL TERHADAP LITERASI NUMERIK SISWA PADA SENI KARAWITAN DI SDN 3 KREBET (Studi Kasus di SDN 3 Krebet Ponorogo) - Nuraini Nuraini; Tirta Dimas Wahyu Negara (TAMUMATRA, 2025)
This study aims to (1) determine the musical intelligence of students in the art of karawitan at SDN 3 Krebet Ponorogo. (2) to determine the numerical literacy of students in the art of karawitan at SDN 3 Krebet Ponorogo. (3) to prove whether there is an increase in musical intelligence so that it can affect the numerical literacy of students in the art of karawitan at SDN 3 Krebet Ponorogo. Musical intelligence plays a role in understanding rhythm patterns, tones, and musical structures, which are related to numerical skills such as pattern calculations and understanding fractions. The art of karawitan, as traditional music that is rich in mathematical elements, can be a tool to improve numerical literacy. The method used is a quantitative approach using the societal correlation method and data analysis techniques. Data on musical intelligence and numerical literacy were obtained from observations, questionnaires, documentation, and the data was processed with a percentage (%). The population in this study were all 32 fourth grade students at SDN 3 Krebet Ponorogo, with purposive sampling (purposeful sampling) which is a non-probability sampling technique where researchers deliberately select individuals or groups that are considered most relevant or useful to answer research questions, the sample used in this study was 18 students. In this study, data collection used a questionnaire to determine how musical intelligence influences numerical literacy in karawitan art at SDN 3 Krebet Ponorogo which was obtained through simple linear analysis techniques. The results of the study showed that there was a significant positive influence between musical intelligence and numerical literacy. The magnitude of the influence of musical intelligence on numerical literacy is 42%. So, musical intelligence influences 42% in numerical literacy in karawitan art at SDN 3 Krebet Ponorogo and the rest is influenced by other factors not included in the study. This study contributes to the development of multiple intelligence theory, especially in the context of the relationship between musical intelligence and numerical literacy. The results of this study are expected to strengthen the theory that non-academic intelligence (such as musical) also has an impact on academic abilities (such as numeracy), as well as add to the literature on the integration of arts and mathematics in elementary education.